The challenges of managing acute myeloid leukemia in pediatric patients: a review of current treatment strategies - Verma, Ashutosh Kumar; Shrivastava, Neha (International Journal of Research in Medical Sciences, 2025)
Acute myeloid leukemia (AML) in pediatric patients presents with complex pathophysiology but a diverse treatment response and so is a difficult disease to treat. Despite substantial progress in genetic profiling of the diseases and precision medicine as well as targeted therapies, pediatric AML continues to be a significant cause of loss of life to cancer in children. Intensive chemotherapy, hematopoietic stem cell transplantation (HSCT), and FLT3 inhibitor are most of the treatment strategies used so far. However, therapeutic efforts are complicated by the high risk of relapse of certain patient subtypes and disease genetic heterogeneity, as well as continually rising incidence of resistance. Novel insight in the field of immunotherapy such as monoclonal antibodies, CAR-T cell therapy, and conjugation of FLT3 inhibitor in therapy hold promise for improved efficacy and decreased toxicity in the recent past. Nevertheless, conventional therapy of pediatric AML is still not an option for these pediatric AML patients with high risk genetic mutation (TP53), so new paradigms in treatment of pediatric AML are required. Then, the current treatment strategies for high risk pediatric AML are reviewed, the challenges in the management of the disease are discussed, and how emerging treatments may improve survival are discussed. The outcomes of genetic mutations, treatment protocols and reviewed combined advantages of current clinical trials is included and made available as valuable insights in pediatric AML treatment on this paper.